Migrating C/C++ Software to Mobile Platforms in the ADM Context - Martinez, Liliana; Pereira, Claudia; Favre, Liliana (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2021)
Software technology is constantly evolving and therefore the development of applications requires adapting software components and applications in order to be aligned to new paradigms such as Pervasive Computing, Cloud Computing and Internet of Things. In particular, many desktop software components need to be migrated to mobile technologies. This migration faces many challenges due to the proliferation of different mobile platforms. Developers usually make applications tailored for each type of device expending time and effort. As a result, new programming languages are emerging to integrate the native behaviors of the different platforms targeted in development projects. In this direction, the Haxe language allows writing mobile applications that target all major mobile platforms. Novel technical frameworks for information integration and tool interoperability such as Architecture-Driven Modernization (ADM) proposed by the Object Management Group (OMG) can help to manage a huge diversity of mobile technologies. The Architecture-Driven Modernization Task Force (ADMTF) was formed to create specifications and promote industry consensus on the modernization of existing applications. In this work, we propose a migration process from C/C++ software to different mobile platforms that integrates ADM standards with Haxe. We exemplify the different steps of the process with a simple case study, the migration of “the Set of Mandelbrot” C++ application. The proposal was validated in Eclipse Modeling Framework considering that some of its tools and run-time environments are aligned with ADM standards.
Keywords: MDE; architecture; mobile device; metamodel; IJIMAI